The relevance of Royce - Parker, Kelly A., 1963-; Bell, Jason (Professor of philosophy) (American philosophy series (Unnumbered), 2014)
In his own day, at Harvard University at the turn of the 20th century, Josiah Royce was one of America's premier philosophical exports, and a prominent interpreter of European and Asian thought. After Royce's death, and after two world wars, the topics dear to him--loyalty, idealism, and systematic metaphysics--faded from mainstream philosophical discussion. Royce's vigorous but sympathetic critiques of pragmatism; his efforts to develop pragmatist-inspired tools of logic and linguistic analysis; his soaring explorations of such themes as loyalty, sorrow, and the modern significance of Christian faith; and his forays into what would later be recognized as "applied ethics" all came to be regarded as obsolete. Now, a hundred years after Royce's heyday, we witness an upwelling of articles, books, and conferences dedicated to exploring the meaning of his thought. The present volume is a collection of perspectives from contemporary philosophers engaged in exploring Royce's work with a fresh eye. An important reason for Royce's recent reemergence--his commitment to the potential of interdisciplinary work in academia--is visible in the broad disciplinary scope that this volume provides.